Induction of immunosuppressive functions and NF-κB by FLIP in monocytes. Issue 1 (December 2018) - Fiore, Alessandra; Ugel, Stefano; Sanctis, Francesco; Sandri, Sara; Fracasso, Giulio; Trovato, Rosalinda; Sartoris, Silvia; Solito, Samantha; Mandruzzato, Susanna; Vascotto, Fulvia; Hippen, Keli; Mondanelli, Giada; et al.
Abstract Immunosuppression is a hallmark of tumor progression, and treatments that inhibit or deplete monocytic myeloid-derived suppressive cells could promote anti-tumor immunity. c-FLIP is a central regulator of caspase-8-mediated apoptosis and necroptosis. Here we show that low-dose cytotoxic chemotherapy agents cause apoptosis linked to c-FLIP down-regulation selectively in monocytes. Enforced expression of c-FLIP or viral FLIP rescues monocytes from cytotoxicity and concurrently induces potent immunosuppressive activity, in T cell cultures and in vivo models of tumor progression and immunotherapy. FLIP-transduced human blood monocytes can suppress graft versus host disease. Neither expression of FLIP in granulocytes nor expression of other anti-apoptotic genes in monocytes conferred immunosuppression, suggesting that FLIP effects on immunosuppression are specific to monocytic lineage and distinct from death inhibition. Mechanistically, FLIP controls a broad transcriptional program, partially by NF-κB activation. Therefore, modulation of FLIP in monocytes offers a means to elicit or block immunosuppressive myeloid cells. Signaling and transcriptional regulation of MDSC activity remains largely undefined. Here the authors show that monocytic MDSC immunosuppression is triggered by c-FLIP and requires NFκB, implicate this axis in cancer prognosis and response to therapy, and employ ectopic FLIP to treat immunopathology.